Stratejik dış ticaret politikaları ve uluslararası rekabet gücü - Uçar, Umut Ulaş (My University, 2017)
Bu çalışmada, stratejik dış ticaret politikaları üzerinde durulmuş,öncelikle tanımı, hangi amaçla, ne için ve ne zaman kullanılması gerektiği anlatılmış, dış ticaret teorisinde diğer modellerden ayıran özelliklerinden bahsedilmiş ve bu politikaların temelini oluşturan, Spencer ve Brender Modeli incelenmiştir. Ardından bu politikalar uygulandığında o, ülke veya sektöre ne gibi fayda sağlayacağı, ne zaman ve nasıl uygulandığında bu faydanın ortaya çıkacağı açıklanmıştır. Japonya, Güney Kore gibi bazı ülkelerin, bu politikaları hangi sektörde ne için kullandıkları, hangi yönlerden bu politikalardan kazanç sağladıkları, dolayısıyla uluslararası arenada diğer firma, sektör ve ülkelere karşı rekabet gücü kazanıp kazanmadıkları anlatılmıştır. Bu bağlamda, özellikle Yeni Dış Ticaret Teorileri çerçevesinde, göstergelere dayalı olarak, bu politikaları uygulayan ülkelerin karşılaştırmalı bir analizi yapılmıştır. Son olarak, Türkiye’nin kalkınma süreci için stratejik ticaret politikaları çerçevesinde çıkarsamalarda bulunmaya çalışılmıştır.

In this study, first of all was focused on strategic foreign trade policies.At this stage, It was mentioned about what the strategic foreign trade policies are, and the definition of the strategic trade policies subsuquently there would have been description of these policies when and for what purpose, and it was mentioned about principle of these policies distinguising them from the other models which are in foreign trade policy, and the ones who paved the way for these policies is only Barbara Spencer and James Brender who are also owner of the Barbara and Brender Model were investigated, and when implemented how and such profits comes out especially how it benefits for a sector or a country overall the time and the way in which these policies whose most principle specialities also benefits how it happens was explained. Last of all the countries some of which implemented to these policies for what these policies used and for what purpose and for which sectors those policies are used too and in what aspects that they profit from these polcies such as Japon, South Kore and so on, accordingly in the international markets and arena towards other firm, sector and countries whether they achieve competetive power or not were indicated particularly within the frame of new foreign trade policy and analysed comparatively the countries of which implemented these policies based on of indicators. As part of strategical foreign trade policies for the process of devoloping of turkey it was tried to find the infrences.
Keywords: Comparative advantage; Dışsallıklar; Ekomi politikası; Eksik Rekabet; Externalities; Free foreign trade policy; Güney Kore; Imperfec competitation; International competetive power; Japonya; Karşılaştırmalı Üstünlük; Oligopol; Oligopolistic market; Ölçek Ekonomileri; Refah; Rekabet, Uluslararası; Scale economies; Serbest Dış Ticaret; Specialization; Strategic foreign trade policies; Stratejik Dış Ticaret Politikaları; Türkiye; Uluslararası Rekabet Gücü; Uzmanlaşma; Welfare; Yeni ticaret teorisi